POTENSI PENGEMBANGAN TRANS PAKUAN SEBAGAI PENERAPAN KONSEP GREEN TRANSPORTATION DI KOTA BOGOR (Jurnal Penelitian Transportasi Darat, 2015)
ABSTRACTThe implementation of Bus Rapid Transit System trough the operation of the Trans Pakuan in Bogor is a form of mass transit improvements as the part of transport development sector based on green transport/sustainable transportation. The development of sustainable transport is an effort to minimize the negative impact of the development of the transport sector, especially in environmental aspects which is associated with emission levels reduction. Some issues encountered in the development of Trans Pakuan is the low service performance identified by the percentage of load factor for corridor 2 was 6.25% and for corridor 3 was 54.17%. The availability of public transportation in the city of Bogor relatively adequate (3,412 units) which became the main factor affecting the service of Trans Pakuan which only has 27 units of fleet to serve 3 corridor. This study aims to analyze the potential for the development of Trans Pakuan as the implementation of the sustainable transportation concept by identifying mode choice opportunities of Trans Pakuan compared to public transportation (angkot) in Bogor. This study used a quantitative method based on quantitative data that analyzed with analysis techniques modal choice (mode choice) binary logit binomial models. The survey was conducted to the respondents who are the users of Trans Pakuan and public transportation (angkot) in Bogor. The conclusions of the study are the variables that gives affect to the modal choice of Trans Pakuan compared with angkot consists of change of modes variable and travel time. The Trans Pakuan modal choice opportunities based on these variables only 2.5% (97.5% chance of urban transport/angkot) with angkot as reference based. The identification of these opportunities showed that the potential for the development of Trans Pakuan as the implementation of sustainable transport concepts still need more improvement, especially for the variable of change of mode and travel time.ABSTRAKPenerapan sistem Bus Rapid Transit melalui pengoperasian Trans Pakuan di Kota Bogor merupakan bentuk perbaikan transportasi massal yang menjadi bagian dari pengembangan sektor transportasi berbasis green transportation/transportasi berkelanjutan. Pengembangan konsep transportasi berkelanjutan tersebut sebagai upaya untuk meminimalkan dampak negatif pengembangan sektor transportasi terutama dalam aspek lingkungan terkait penurunan tingkat emisi. Kendala yang dihadapi dalam perkembangan pengoperasian Trans Pakuan adalah kinerja pelayanan yang masih rendah ditandai dengan persentase load factor koridor 2 sebesar 6,25% dan koridor 3 sebesar 54,17%. Ketersediaan angkutan kota di Kota Bogor yang relatif telah memadai (3.412 unit) menjadi faktor utama yang mempengaruhi layanan Trans Pakuan yang hanya memiliki 27 unit armada yang melayani 3 koridor. Penelitian ini bertujuan untuk menganalisis potensi pengembangan Trans Pakuan sebagai penerapan konsep transportasi berkelanjutan dengan mengidentifikasi peluang pemilihan moda Trans Pakuan dibandingkan dengan angkutan kota di Kota Bogor. Penelitian ini menggunakan metode kuantitatif berdasarkan data kuantitatif yang dianalisis dengan teknik analisis pemilihan moda (mode choice) model binomial logit biner. Survei dilakukan pada responden yang merupakan pengguna Trans Pakuan dan angkutan kota di Kota Bogor. Kesimpulan yang dihasilkan adalah variabel yang berpengaruh terhadap pemilihan moda Trans Pakuan dibandingkan dengan angkutan kota terdiri dari variabel pergantian moda dan waktu tempuh. Adapun peluang pemilihan moda Trans Pakuan berdasar variabel tersebut dengan based reference angkutan kota hanya 2,5% (peluang angkutan kota 97,5%). Identifikasi peluang tersebut menunjukkan potensi pengembangan Trans Pakuan sebagai penerapan konsep transportasi berkelanjutan masih memerlukan perbaikan terutama pada aspek pergantian moda dan waktu tempuh.